The Unconscious as a Formative Aspect of the Sexuality of the Character DSD in the Comic Houkago Hokenshitsu by Mizushiro Setona - Aulia Rahman (Universitas Diponegoro, 2024)
Disorder of Sex Development (DSD) encompasses conditions where individuals face challenges in determining their sexual identity, often deviating from the binary gender norms prevalent in society. This research delves into the portrayal of sexual identity formation among DSD individuals, specifically in the manga 'Houkago Hokenshitsu' by Mizushiro Setona. This research is conducted by applying qualitative research methods, research analysis is described or described through written words. The study aims to elucidate the process through which DSD characters navigate their sexual identity within a dream world, while also exploring the interplay between sexual identity, DSD, and feminist psychoanalytic perspectives presented in the comic. Drawing upon Juliet Mitchell's theoretical framework of Unconsciousness and Neurosis as expounded in 'Psychoanalysis and Feminism: A Radical Reassessment of Freudian Psychoanalysis' (2000), this research underscores the significant role of the unconscious mind in shaping individual identity. Mitchell contends that unconscious processes profoundly influence one's psyche, often manifesting in symptoms of hysteria-induced Neurosis, such as anxiety. The findings of this study reveal two key insights: Firstly, the engagement and exploration of the dream realm facilitate the DSD character in crystallizing their desired sexual identity for real-world expression. Secondly, this journey towards self-identification within the dream world precipitates symptoms of neurotic anxiety, stemming from societal pressures and the internal struggle for self-acceptance and autonomy in reconstructing their sexual identity. In essence, this research underscores the intricate dynamics between sexual identity formation, DSD experiences, and the psychological ramifications portrayed in 'Houkago Hokenshitsu', shedding light on the complexities inherent in the quest for personal identity and acceptance. Keywords: DSD; Dreams; Sexual Identity; Feminist Psychoanalysis <a href=